2016
DOI: 10.1071/ah15047
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilisation by people living with chronic non-cancer pain: findings from the Pain and Opioids IN Treatment (POINT) study

Abstract: Objective. The aims of the present study were to describe the use, and barriers to the use, of non-medication pain therapies and to identify the demographic and clinical correlates of different non-opioid pain treatments.Methods. The study was performed on a cohort (n = 1514) of people prescribed pharmaceutical opioids for chronic noncancer pain (CNCP). Participants reported lifetime and past month use of healthcare services, mental and physical health, pain characteristics, current oral morphine equivalent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Extant literature documents that opioid users report severe pain [64], and have higher healthcare utilization compared with non-opioid users [38,65,66]. Our findings suggest that similarly to other chronic pain conditions, MFS individuals who use opioids report more intense, frequent, and non-remitting pain.…”
Section: Physical and Psychological Burden In Opioid Userssupporting
confidence: 60%
“…Extant literature documents that opioid users report severe pain [64], and have higher healthcare utilization compared with non-opioid users [38,65,66]. Our findings suggest that similarly to other chronic pain conditions, MFS individuals who use opioids report more intense, frequent, and non-remitting pain.…”
Section: Physical and Psychological Burden In Opioid Userssupporting
confidence: 60%
“…For example, 34% of a cohort of CNCP participants reported that there had been no clinically significant change in their activity limitations, symptoms, emotions and overall quality of life since starting opioids 23. Significant proportions of the cohort were using complementary or alternative interventions for their pain which have limited or no evidence of efficacy in chronic pain 23 24. In addition, they often report that attending physiotherapy, specialised exercise classes or psychotherapy was often prohibitively expensive and unfunded whereas medicines and general practitioner (GP) visits are at least partially covered by the Australian Medicare and Pharmaceutical Benefits Schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The mean of pain scores suggested a significant reduction has been significantly increased (Figure 5). The results shed light on CAM potential positive effects on chronic pain management and further limiting analgesic misuse that were found in some research [13,16,27].…”
Section: Resultsmentioning
confidence: 59%